(untitled) (Brazilian Journal of Radiation Sciences, 2021)
Brazilian National Nuclear Energy Commission – CNEN – is responsible to build a repository for the low and intermediate–level radioactive wastes generated in Brazil. In accordance of Brazilian legislation it will be a near surface one. In the repository, treated waste will be stored, which will be surrounded by engineering and natural barriers, in order to prevent the release of radionuclides, during the required time to their decay to the limit levels. The focus of this study is to characterize the expanded vermiculite, which can be used as a natural barriers, over and under the engineering barriers and also as a backfill. They have the function of limiting water infiltration and stabilizing the disposal system, filling the empty spaces, controlling the gases and delaying the release of radionuclides. In this paper is presented the characterization of an expanded vermiculite. The tests to determine its physical chemical properties were based on a clay characterization Protocol. The granulometric analysis was performed using a sieving method. The moisture content was established by the gravimetric method of weight loss, and the specific surface area by the BET method. The helium ultrapicnometer method was used to determine the density. The microstructure was analyzed by X-ray diffraction and scanning electron microscopy. The results indicate that the studied vermiculite would be efficient as a natural barrier of the Brazilian surface repository, as the it presented a stable structure.